The social construction of adolescents plays a role in the transmission of the socio-cultural value - Ratulangi, Ziva Syah; Utomo, Cahyo Budi; Sunarto, Sunarto (Universitas Negeri Semarang, 2021)
This study aims too see the extent to which the social construction of adolescents plays a role in the transmission of the socio-cultural value of Al-Hidayah art. Departing from the problem of the transmission of the value of art and culture Dendang Al-Hidayah has not been optimal. This research uses qualitative research type, phenomenological and ethnographic approach, with informant selection tecniques using purposive sampling. Important findings in this study include; the results showed the social value contained in the art and culture of Dendang is the value time discipline, mutual respect, delibration, and cooperation. There is no program from the village, the Board of Indigenous Deliberation, and the Education and Culture Office of South Bengkulu Regency to transmit the art of drums to teenagers. The social construction of the transmission of the social value of Dendang art and culture is as the ethical values growth through the transmission of social values of Dendang. Obstacles in the transmission of Dendang art (1) lack of public interest in the art of Dendang (2) the absence of village programs, the Board of Coustomary Delibrations, and the Education Office of South Bengkulu Regency. The theoretical analysis uses social construction theory. The theoretical analysis uses social construction theory.